Understanding the progress and challenges in the fields of thermo-catalysis and electro-catalysis for the CO2 conversion to fuels - V. S. K. Yadav (17727660) (2023)
The need to limit anthropogenic CO2 emissions and lower the atmospheric CO2 concentration makes CO2 conversion an imminent requirement. Availability of suitable facilities and prior understanding how electro and thermal catalysis work renders them as appealing platforms for conversion of CO2. Catalysts play a crucial part in the conversion of CO2 to chemicals in both processes. Catalysis is a process initiated by the interaction of reactants, intermediates, and products produced on the catalyst’s surface. Generally, higher temperatures in thermo-catalytic process or electrical potentials in electrocatalytic process are used to increase the reaction rate to get the desired results and to overcome the kinetic barrier. Several studies have been reported in both the processes with a desire to decrease the atmospheric CO2 concentration by stopping CO2 emissions at the site of generation itself. The viability of catalytic performance in both situations for the large-scale conversion of CO2 is still up for debate. In this review, we intend to focus on recent developments in CO2 conversion aided by diverse catalysts by analyzing and comparing proof-of-principle investigations on applied conditions, catalyst activity and stability for thermocatalytic and electrocatalytic CO2 conversions. The most common catalyst synthesis techniques employed in both experiments were analyzed. Primary goal of this review is to draw connections between the two felds in order to generate fresh insights that will lead to a more efcient and integrated CO2 conversion process. Other Information Published in: Emergent Materials License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s42247-023-00606-9